Announcement of CLA Learning Network Launch - Lab, Learning (2016)
USAID’s Bureau for Policy, Planning and Learning (PPL), together with the Bureau for Economic Growth, Education, and Environment’s localwork s program, is pleased to announce the launch of a Learning Network foc used on building the evidence base for Collaborating, Learning and Ada pting (CLA).